Purposeful SDM: A problem-based approach to caring for patients with shared decision making. Issue 10 (October 2019) - Hargraves, Ian G.; Montori, Victor M.; Brito, Juan P.; Kunneman, Marleen; Shaw, Kevin; LaVecchia, Christina; Wilson, Michael; Walker, Laura; Thorsteinsdottir, Bjorg
Highlights: The focus on patient involvement in SDM downplays the role of patient problems. Purposeful SDM is a problem focused SDM approach. SDM may be a range of decision making methods varying with patient problems. Methods to: weigh alternatives, negotiate desires, problem solve, develop insight. New measures and tools corresponding to different SDM purposes are required. Abstract: Objective: Patient involvement focused the growth of Shared Decision Making (SDM) in contemporary healthcare practice, research, and education. Whilst important, securing appropriate patient involvement or equipping patients to choose is not necessarily the principal purpose of SDM. The purpose of SDM like all medical decision making is to act well in response to a patient's problem, broadly conceived. In which situations and how SDM addresses patient problems is unclear. We seek to develop a purposeful approach to SDM that is oriented to the kinds of problems that SDM might help resolve. Methods: Through vignettes of the experience of a patient, Rachel we demonstrate different kinds of situations in which Rachel, her family, and clinicians need to make decisions together. Results: Different methods of SDM are needed in situations of: Uncertain harms and benefits. Intra or interpersonal conflict. Intellectual, practical, and emotional incoherence. Existential transition. Conclusion: SDM may be understood as a range of methods that vary substantially with patients' situations and the purpose that they pursue. Practice Implications: Clinicians struggle to adopt SDM when they do not see it as relevant to clinical work. Orienting SDM to the problems that patients and clinicians routinely face may further SDM adoption, education, and research.